Finite-rate chemistry modelling of non-conventional combustion regimes. (December 2017) - Li, Zhiyi; Cuoci, Alberto; Sadiki, Amsini; Parente, Alessandro
Abstract: The present work deals with the numerical simulation of Adelaide Jet in Hot Co-flow burner under Moderate or Intense Low oxygen Dilution (MILD) conditions, using the Partially Stirred Reactor (PaSR) model for turbulence-chemistry interactions. The PaSR model assumes that reactions are confined in specific regions of the computational cells, whose mass fractions depend both on the mixing and the chemical time scales. Therefore, the appropriate choice of mixing and chemical time scales becomes crucial to ensure the predictivity of the numerical simulations. Results show that the most appropriate choice for the evaluation of the mixing time scale in MILD regime consists in using the geometric mean of the Kolmogorov and the integral mixing time, rather than Kolmogorov or integral scales. This is supported by the validation of the numerical results against experimental profiles of temperature, major and minor species mass fractions. Moreover, the identification of the key species in the oxidation process allows to determine a chemical time scale that improves the prediction of centerline and upstream temperature predictions, compared to the results obtained by including all species in the evaluation of the chemical scale.